Comparative study of each surgical step in radical prostatectomy under 3D and 2D laparoscopy - Zhang, Pengcheng; Pei, Yuhan; Zhi, Yunlai; Song, Ninghong; Sun, Fanghu (Frontiers in Surgery, 2024)
Comparing the specific advantages and surgical outcomes of each step in radical prostatectomy under 3D versus 2D laparoscopy.Methods: From October 2019 to January 2023, our urology department treated 63 cases of prostate cancer, using an odd-even arrangement method to divide into two groups. This is a non-randomized prospective study, with 33 odd-numbered cases in the 3D group and 30 even-numbered cases in the 2D group. The surgery was divided into four steps: (1) establishing an extraperitoneal pneumoperitoneum (2) pelvic lymph node dissection (3) excising the prostate(4) bladder-urethral anastomosis, comparing the two groups in terms of surgical time, blood loss, and relevant postoperative indicators for each step.Results: All 63 surgeries were successfully completed without any conversions. Comparing 3D and 2D laparoscopy groups, there were statistically significant differences in total surgery time (123.5±15.3 min vs 145.6±17.2 min, P＜0.05), total blood loss (198.3±18.4 ml vs 243.1±20.1 ml, P ＜ 0.05), prostate excision time (55.1±8.4 min vs 67.2±9.3 min, P ＜ 0.05) and blood loss (101.6±12.2 ml vs 123.8±14.1 ml, P＜0.05), bladder-urethral anastomosis time (30.5±4.3 min vs 37.6±5.1 min, P＜0.05) and blood loss (62.7±9.7 ml vs 82.5±8.2 ml, P＜0.05). There were no statistical differences in the time and blood loss during the establishment of extraperitoneal pneumoperitoneum and the cleaning of pelvic lymph nodes (P ＞ 0.05). In terms of urinary incontinence rates, the 3D laparoscopy group was lower than the 2D group, and in terms of preserving erectile function, the 3D group was higher than the 2D group, with significant statistical differences (P＜0.05). There were no statistically significant differences between the two groups in terms of postoperative drainage days, hospitalization days, hospitalization costs, time of catheter removal and positive margin rates (P＞0.05).Compared to traditional 2D laparoscopy, 3D laparoscopy can shorten the operation time and reduce bleeding in the steps of prostate excision and bladder-urethral anastomosis, but there was no significant difference in peri-operative outcomes.